2010
DOI: 10.1111/j.1549-0831.2010.00019.x
|View full text |Cite
|
Sign up to set email alerts
|

Community Context, Land Use, and First Birth

Abstract: This paper examines the influence of community context and land use on the monthly odds of first birth in a society in the midst of dramatic fertility transition. The theoretical framework guiding our work predicts that proximity to non-family services should delay first births by creating opportunities for competing non-family activities and spreading new ideas that change expectations about family life. On the other hand, living in agricultural settings that provide opportunities for higher returns to the ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 100 publications
2
19
0
Order By: Relevance
“…By controlling for the presence of markets, employers, health services, and public transportation I demonstrate that the characteristics of the natural environment themselves are related to fertility behaviors, independently of how the rest of the physical environment has changed. These findings are in line with previous research in this setting looking at the independent effects of non-family organizations and land use (Ghimire and Axinn 2010). In substantive terms these results imply that for residents, a “better” neighborhood is one rich in both social support services and natural resources.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…By controlling for the presence of markets, employers, health services, and public transportation I demonstrate that the characteristics of the natural environment themselves are related to fertility behaviors, independently of how the rest of the physical environment has changed. These findings are in line with previous research in this setting looking at the independent effects of non-family organizations and land use (Ghimire and Axinn 2010). In substantive terms these results imply that for residents, a “better” neighborhood is one rich in both social support services and natural resources.…”
Section: Discussionsupporting
confidence: 92%
“…Because we have 10 years of monthly contraceptive use data, women who were only 15 years old in 1996 would have been 25 at the end of the data collection period. Since mean age at marriage is around 20, with childbearing typically occurring shortly thereafter, this is plenty of time to observe the transition to using contraception (Ghimire and Axinn 2010). …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Empirical evidence from rural Nepal is consistent with this idea (Axinn and Yabiku 2001; Ghimire and Axinn 2010): the spread of mass education has led to delays in marriage (Yabiku 2005), a transition away from arranged marriage toward individual choice of spouse (Ghimire et al 2006), and an increase in positive relations between spouses (Hoelter et al 2004; Allendorf and Ghimire 2013). Moreover, research has repeatedly demonstrated that exposure to formal education and Western European-style curricula are among the most powerful forces affecting family formation and relationships (Caldwell et al 1988; Hoelter et al 2004; Lin 1994).…”
Section: Discussionmentioning
confidence: 88%
“…Community agents in the Chitwan ABM represent a cluster of (usually ten to twenty) households that live in close proximity and share common community context-defined as similar access to markets, employment opportunities, schools, bus stops, and health centers. The inclusion of this additional level in the Chitwan ABM is due to the abundant research in Chitwan about how community context might affect demographic and land use decisions (e.g., Axinn et al 2007;Ghimire and Axinn 2010;Axinn and Ghimire 2011).…”
Section: Structure Of Agentsmentioning
confidence: 99%